Tactics in movement: pursuing social inclusion in transnational migration - Frangella, Simone (2018)
Within the social webs comprising migratory movement, mutual-help and forms of cohabitation prove to be fundamental for their creation and maintenance. Both in the sphere of national and international migration, overlapping or running in parallel with forms of State agency or even the illegal networks that emerge in this area, these support relations are a crucial axis of the circulation composing the dynamics of migration, as a collective fact and an individual itinerary (Menezes and Godoi 2011; Martes 1999). Whether in search of new forms of family-based economic reproduction, or due to “going out into the world” seeking social experience of a diverse order, migrants create trajectories that are contingent upon exchanges, favours and interactions between relatives, friends from the place of origin and new ones met along the travelled route. This process involves an intense movement of people, assets and information. It continuously redefines and creates the social relations and significance of place that characterise the daily experiences of these individuals (Olwig 2007).